New educational approach for the sustainability of natural forest capital: review, analysis and conceptual contributions on the natural capital of the Romerillo forest (Scientia Agropecuaria, 2024)
The concept of Natural Capital of the Romerillo forests (NCR) has been little studied in relation to the Education of this important type of natural capital. However, currently, many researchers have argued that Education can contribute significantly to the teaching and learning of this natural capital. By investigating how the concept has been studied, this article has attempted to establish the direction, understanding and use of Education that the NCR may take in the future, within the context of research into an Intangible Creative Ecological Economy (ICEE). This study used an exploratory research methodology with secondary information, in combination with chronological, conceptual and thematic literature review techniques. The literature review indicates that Education on NCR has been used in three areas of research to explain or address a particular construct: (1) promotion of formal and informal programs for use of the intangible environmental services, (2) development of an ICEE that promotes biotrade of intangible services from the Romerillos forests, and (3) short- and long-term conservation of the Romerillos forests. For future studies, it is recommended to address the concept of Education in “Intangible Forest Natural Capital” as a strategy for the sustainable use of the intangible environmental services of the NCR, aiming to mitigate deforestation and preserve the forests of the Romerillos Andean.